Moi, un Noir - Rouch, Jean (France : Films de la Pléiade, 1959)
The lives of young Nigerian émigrés in Treichville on the Ivory Coast. The hero is Edward G. Robinson, a young Nigerian, who has no job, no place to live. He crosses the lagoon in a small motorboat and gets off at Treichville. Different activities of Nigerians in Abidjan. Unskilled laborers, porters, dock workers, and "coaxers"—men who coax passengers into trucks. Robinson's two best friends, Tarzan and Eddie Constantine, are a taxi driver and a peddler–cloth merchant, respectively. Robinson and his friend Eddie are looking for work as occasional laborers. Robinson keeps his eye on the hiring at the entrance to the port where once in a while he works all day loading sacks of coffee. At noon he has lunch at the Hotel des Bozeri, sleeps in the street, and returns to his work, reminded of his military campaigns. In the evening he goes back to the "Nigerian Fraternity," where they gamble away the day's wages at cards. He tells stories about the granddaughters of the chief of the Nigerian community, and goes to the Ambiance bar to find Tarzan in his boxing workout. Eventually the three friends go back down to the edge of the lagoon, which reminds them of their Niger homeland. Robinson becomes more and more bitter. Heading back to Treichville, on the banks of the lagoon, he recalls his military life and the war in Indochina, and philosophizing all the while, he crosses the new bridge, telling "Little Jules" that maybe the future will be better. Introduction by Bernard Surugue.